Brand seduction how neuroscience can help marketers build memorable brands - Weber, Daryl (Career Press, 2016)
" For many marketing professionals, "science" is a four-letter word. They see brand-building as an unteachable art guided by their intuition and experience. But at its core, marketing aims to seed ideas into people's minds, make them feel a certain way, and, ultimately, get them to act. In Brand Seduction, Daryl reveals the latest psychological and neuroscientific discoveries about how our minds process brand information and make decisions, and the important roles our emotions and unconscious play in our selections. Welcome to the new world of neuromarketing. Through simple language, engaging stories, and real-world examples, Brand Seduction shows you how to decode, build, and use these hidden brand fantasies to grow your brand and business. You'll learn: The surprising unconscious side of brands. The biggest myths about consumer psychology. The real role of emotions in building brands. Practical tools to use neuroscience to inspire better marketing. Everyone seems to have a different idea of what brands are, how they work, and how they are built. Brand Seduction digs deeper into the nature of brands, how they exist and behave in the mind, and how marketers and business leaders can use this understanding to "seduce" customers and grow their businesses."--Provided by publisher.